2012
DOI: 10.1136/archdischild-2012-302051
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the risk of boys with isolated cryptorchidism developing testicular cancer in later life

Abstract: Boys with isolated cryptorchidism are three times more likely to develop testicular cancer. The limitations of this study must be acknowledged, in particular, possible publication bias and the lack of high-quality evidence focusing on the risk of malignancy in boys with isolated cryptorchidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
79
0
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(91 citation statements)
references
References 32 publications
2
79
0
10
Order By: Relevance
“…Lebanese patients are diagnosed at 32 years of age, most commonly at an early stage with testicular lump being the most common presenting complaint followed by unspecific sensation of pain or heaviness similar to the published data (Garner et al, 2005). We attribute the increased percentage of early diagnosis to the high level of awareness and anxiety that affect young Lebanese patients upon detection of a testicular lump or pain (Saab et al, 2014).Similarly to our experience, cryptorchidism is the most established risk factor for testicular cancer occurring in 5-10% of patients (Ferguson and Agoulnik, 2013;Lip et al, 2013Lip et al, , p. 2013. Pathologic stratification of the testicular tumors showed that NST were almost twice more prevalent than the seminomatous subtype and that almost two-thirds of the NST were mixed germ cell tumors.…”
Section: Discussionsupporting
confidence: 88%
“…Lebanese patients are diagnosed at 32 years of age, most commonly at an early stage with testicular lump being the most common presenting complaint followed by unspecific sensation of pain or heaviness similar to the published data (Garner et al, 2005). We attribute the increased percentage of early diagnosis to the high level of awareness and anxiety that affect young Lebanese patients upon detection of a testicular lump or pain (Saab et al, 2014).Similarly to our experience, cryptorchidism is the most established risk factor for testicular cancer occurring in 5-10% of patients (Ferguson and Agoulnik, 2013;Lip et al, 2013Lip et al, , p. 2013. Pathologic stratification of the testicular tumors showed that NST were almost twice more prevalent than the seminomatous subtype and that almost two-thirds of the NST were mixed germ cell tumors.…”
Section: Discussionsupporting
confidence: 88%
“…6 In addition, it has been shown that UDT inhibits the differentiation of primitive germ cells, starting at 4 to 12 months, which is crucial for the production of germ cells that subsequently enable spermatogenesis. 7 Delayed repositioning of an undescended testis may result in a reduction in germ cell development and low testicular volume, potentially diminishing subsequent fertility.…”
mentioning
confidence: 99%
“…[71][72][73][74] An abdominal or inguinal position of the gonads represents an additional risk factor. 75 The informed decision of the parent/patient for performing gonadectomy is based on the GCC risk and the sex of rearing. 76 In boys with partial gonadal dysgenesis, Leydig cell function may be sufficient for spontaneous pubertal development [77][78][79] and, therefore, the current practice is to leave the gonads in place.…”
mentioning
confidence: 99%